IoT based Accident Prevention system on High Altitude integrated with Android Application enabled with emergency Service Facility - Nathaniel, Divya Ebenezer; Panesar, Sonia (International Journal of Computer Sciences and Engineering, 2021)
In today’s fast era, vechicle accidents are considered to be the main agony faced all over the world that may be due to steep turns present in high altitudes dense population or traffic hazards. Although there are many distinct reasons behind automobile accidents, maximum accidents arise in hilly areas due to uncontrolled speed and ignorance of steep turns by the driver. More often youth just like the pace and when they drive they forget everything around them like vehicles coming from another side, steep turn present in high altitude, sometimes visibility is poor due to pollution and other atmospheric hazards. And if accident occurs, there appears to be a trouble attaining the emergency service at certain locations in mountainous areas or it is difficult to spot the place of accident in time for lack of know-how. As an answer, the integration of internet of things (IoT) and android application technologies can reduce the quantity of accidents and improve the emergency service provider facility for the travellers travelling to hilly areas. In this paper, a clever app is designed that anyone (service provider or traveller) can download and register and get the emergency contact service provider nearby and it will monitor the distance between the car and other vehicle coming from other side using a distance sensor at the steep turns present in high altitudes. It also notifies the traveller with a push message having temperature and weather information so that driver can be warned to keep a track of pace and reduce it gradually.